2010
DOI: 10.1007/s11160-010-9166-6
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the taxonomic status of Merluccius spp. in the northeastern Pacific: a combined morphological and molecular approach

Abstract: The taxonomic status of hake (Merluccius spp.) in the northeastern Pacific is unclear. Hakes in this region are Merluccius productus, M. angustimanus, M. hernandezi, and a morphotype known as dwarf hake. Of these, only the first two species are currently valid. Descriptions in previous studies have been limited by overlapping morphological characteristic, lack of biological material, and limited numbers of sampling localities. To clarify their taxonomy, 461 hake were obtained from eight localities along the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…Furthermore, the BIN system is built on prior studies that have established that most animal species show <2% intraspecific variation in coI , but >4% divergence from their nearest neighbour (Ratnasingham & Hebert, ). The within‐BIN maximum K2P distances were <2% for the present study (1·57 for BOLD:AAB5094 and 1·16 for BOLD:AAA8613), agreeing with previous studies that revealed low divergences between M. angustimanus , M. gayi and M. productus (Silva‐Segundo et al , ) and between M. merluccius and M. senegalensis (Quinteiro et al , ; Campo et al , ). On the other hand, the BIN analysis recognized two taxonomic units in the sequences studied here, which agree with the current taxonomic classification.…”
Section: List Of Argentinean Specimens Of Merluccius Barcoded Barcodsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, the BIN system is built on prior studies that have established that most animal species show <2% intraspecific variation in coI , but >4% divergence from their nearest neighbour (Ratnasingham & Hebert, ). The within‐BIN maximum K2P distances were <2% for the present study (1·57 for BOLD:AAB5094 and 1·16 for BOLD:AAA8613), agreeing with previous studies that revealed low divergences between M. angustimanus , M. gayi and M. productus (Silva‐Segundo et al , ) and between M. merluccius and M. senegalensis (Quinteiro et al , ; Campo et al , ). On the other hand, the BIN analysis recognized two taxonomic units in the sequences studied here, which agree with the current taxonomic classification.…”
Section: List Of Argentinean Specimens Of Merluccius Barcoded Barcodsupporting
confidence: 92%
“…). Previous DNA mitochondrial studies [cytochrome b ( cytb ), control region and 16S rDNA] also pointed out high genetic distances between M. hubbsi and M. australis (Tamura‐Nei: 7·8% in Quinteiro et al (); K2P: 4·2% in Campo et al (); Tamura‐Nei: 1·7 to 4·8% in Silva‐Segundo et al ()).…”
Section: List Of Argentinean Specimens Of Merluccius Barcoded Barcodmentioning
confidence: 94%
See 1 more Smart Citation
“…Nonetheless, this species is not significantly distributed in the surrounding areas between PE‐BSV (Funes‐Rodríguez et al., ; Moser et al., ), which could imply the distribution of two spawning stocks in the CCS (Bailey, Francis, & Stevens, ; Funes‐Rodríguez et al., ). However, genetic studies on M. productus suggested a lesser degree of intra‐specific variation between Washington and Costa Rica (Silva‐Segundo et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Distribution: New South Wales and Victoria (Day et al, 1995), Poland (Poniewozik, 2009), Czech Republic (Kocarkova et al, 2004 and Singapore (Pham et al, 2011). Distribution: Romania (Caraus, 2012), Spain (Alvárez-Cobelas, 1984), Mexico (Valadez et al, 2010), Brazil (Alves-da-Silva and Menezes, 2010), Sierra Leone (Alfinito, 2011), China (Hu and Wei, 2006) and Taiwan (Shao, 2009 Starmach (1983;page 192, figure 388) Description: Cells longitudinally oval, 87-102 µm long, 42-46 µm, wide, narrowed at posterior end into long appendix ca. 31-33 µm long; periplast longitudinally striated, paramylon grains ring-shaped, one large located in cell centre, smaller located in lower part of cell; chloroplasts small, without pyrenoids ( Figure 2i).…”
Section: Trachelomonas Aspera Amcunhamentioning
confidence: 99%